2006
DOI: 10.1007/s00122-006-0438-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of two powdery mildew resistance genes in einkorn (Triticum monococcum L.) accessions

Abstract: Powdery mildew is a severe foliar disease for wheat and could cause great yield loss in epidemic years. To explore new powdery mildew resistance genes, two einkorn accessions including TA2033 and M80, both resistant to this disease, were studied for the inheritance of resistance. Each accession possessed a single but different dominant resistance gene that was designated as Mlm2033 and Mlm80, respectively. Marker mapping indicated that they are both linked to Xgwm344 on the long arm of chromosome 7A. To establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 25 publications
1
61
1
3
Order By: Relevance
“…It is very useful and promising plant breeding material for its resistance to disease (rusts, powdery mildew) (1)(2)(3)(4)(5)(6)(7)(8). The crop is suitable for low input systems -organic farmingbecause of its better adaptability in marginal areas (in comparison with other crops) (1,9).…”
Section: Introductionmentioning
confidence: 99%
“…It is very useful and promising plant breeding material for its resistance to disease (rusts, powdery mildew) (1)(2)(3)(4)(5)(6)(7)(8). The crop is suitable for low input systems -organic farmingbecause of its better adaptability in marginal areas (in comparison with other crops) (1,9).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers, however, can be employed for breeding powdery mildew resistant varieties. In the present study, we identified a Yao et al (2007) have also been reported to be allelic to Pm1, based on the markers linked to these genes. Pm37 has been reported to be closely linked to Pm1.…”
Section: Discussionmentioning
confidence: 54%
“…In order to saturate the regions carrying the powdery mildew resistance genes, primers designed from RFLP probes, MAG1714, MAG2166, MAG2185, MAG1757 and MAG1759, reported to be linked with powdery mildew resistance genes on chromosome 7A (Yao et al 2007), were analysed on the RIL population. In addition, 38 primers designed from ESTs and 20 SSR primers already mapped on the distal half of 7AL (Somers et al 2004) were analysed for parental polymorphism.…”
Section: Marker Enrichment On Chromosome 7al Of Tb5088/tm14087 Ril Pomentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the yield losses range from 13 to 34% under high infestation in the field but during epidemic seasons, the disease can cause up to 50% yield loss (Yao et al, 2007;Zhang et al, 2008;Li et al, 2011;Alam et al, 2013;Quijano et al, 2015;Yu et al, 2015). The shift in pathogenic virulence structures range from the southwest and the southeast coastal regions of China to almost all the wheat growing areas throughout the country and the damage exceeds any other known wheat disease (Liu and Shao, 1994;Luo et al, 2009;Cao et al, 2013;Zhao et al, 2013;Shen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%